2021
DOI: 10.29333/iji.2021.14432a
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Problem-Solving Skills among Secondary Science Students through Problem Based Learning

Abstract: This research was informed by a constructivist approach to learning, with a focus on answering the research question: what skills can science teachers promote and encourage among students through designing and implementing problem-based learning in their classrooms? The research was carried out in a co-education secondary school in England and involved fifty-two Key Stage 3 students (second year of secondary education), aged 13 years old. It utilized a theoretical framework of the 3C3R model (3C-content, conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Reading materials that students have prior knowledge of and can easily relate to their own experiences suggests attracting their interests, activating their cognitive and affective functioning and helping them comprehend texts (Dong et al, 2022). A previous study also emphasized that integrating students' prior knowledge in learning materials is valuable for promoting students' problem-solving skills (Magaji, 2021). The students' cognitive skills in comprehending the texts were mainly seen in the case of this study.…”
Section: Discussionmentioning
confidence: 56%
“…Reading materials that students have prior knowledge of and can easily relate to their own experiences suggests attracting their interests, activating their cognitive and affective functioning and helping them comprehend texts (Dong et al, 2022). A previous study also emphasized that integrating students' prior knowledge in learning materials is valuable for promoting students' problem-solving skills (Magaji, 2021). The students' cognitive skills in comprehending the texts were mainly seen in the case of this study.…”
Section: Discussionmentioning
confidence: 56%
“…Research competencies of undergraduate physics students as a special personality trait, representing a balanced combination of stable motivation to conduct physical research and the ability to perform research work using physical methods, it is advisable and possible to form, using mini-studies as part of a laboratory workshop in general physics.The organization of such mini-studies increases the level of formation of research competencies of physics students of junior courses and prepares them for independent research work at the senior courses of the university. As a result, this increases the level of formation of research competencies of university graduates (Magaji, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Goodnough [36] echoed working in larger groups as part of the challenges of PBL. Others assert that the success of PBL depends on the following factors: the context of the problem, purposeful learning, and personal habits [37]; time spent on tasks and the learning sequence [12,35,38]; the creation of a culture of collaboration and interdependence to scaffolding students' learning [39]; a shift from teachers being the knowledge transmitters to the facilitators of learning by supporting students' independence [40]. These inconsistencies in terms of designing PBL call for a greater understanding and implementation of this pedagogy in preservice science teachers' training.…”
Section: The Challenges Of Implementing Pbl In the Classroommentioning
confidence: 99%
“…Studies have shown that teachers' pedagogical knowledge is a limiting factor in promoting problem-based learning in the classroom [38,41,42]; therefore, it is sparingly implemented by secondary school teachers [43], especially in science lessons. Peterson and Treagust [44] contend that PBL has not been extensively used in science teacher education, and little work has been carried out to study how PBL can be used in preparing preservice science teachers to teach science in their classrooms [45].…”
Section: The Challenges Of Implementing Pbl In the Classroommentioning
confidence: 99%